2020
DOI: 10.1080/13880209.2020.1750658
|View full text |Cite
|
Sign up to set email alerts
|

Emodin in Rheum undulatum inhibits oxidative stress in the liver via AMPK with Hippo/Yap signalling pathway

Abstract: Context: Emodin is a compound in Rheum undulatum Linne (Polygonaceae) that has been reported to exert anti-inflammatory, antibacterial, and antiallergic effects. Objective: Oxidative stress is a causative agent of liver inflammation that may lead to fibrosis and hepato-carcinoma. In this study, we investigated the antioxidant effects of emodin and its mechanism. Materials and methods: We used the hepatocyte stimulated by arachidonic acid (AA) þ iron cotreatment and the C57B/6 mice orally injected with acetamin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 42 publications
(61 reference statements)
0
36
0
Order By: Relevance
“…Emodin (1,3,8trihydroxy-6-methylanthraquinone) (Fig. 1), a natural anthraquinone derivative, is the main active component and the quality control index of RP [16,17]. Emodin has been shown to have various biological activities, such as hepatoprotective, anticancer, antibacterial, neuroprotective, antidiabetic, antiin ammation, and anti-oxidants [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Emodin (1,3,8trihydroxy-6-methylanthraquinone) (Fig. 1), a natural anthraquinone derivative, is the main active component and the quality control index of RP [16,17]. Emodin has been shown to have various biological activities, such as hepatoprotective, anticancer, antibacterial, neuroprotective, antidiabetic, antiin ammation, and anti-oxidants [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Emodin (1, 3, 8-trihydroxy-6-methylanthraquinone) is a natural anthraquinone derivative, and is the main ingredient of many herbs including rhubarb, polygonum multiflorum , and polygonum cuspidatum ( Dong et al., 2016 ; Monisha et al., 2016 ). Pharmacological studies have shown that emodin, as a polyvalent molecule, has a variety of biological functions, such as anti-inflammatory ( Li X. et al., 2020 ; Xu et al., 2020 ), anti-bacterial ( Ji et al., 2020 ), anti-cancer ( Wu C. et al., 2019 ; Ma et al., 2020 ; Rossi et al., 2020 ) and inhibition of oxidative stress( Lee et al., 2020 ). Emodin has also been shown to have potent anti-cardiovascular activities in vitro and in vivo , including anti-inflammatory ( Wu et al., 2007 ), antioxidant damage ( Du and Ko, 2005 ), inhibition of myocardial cell fibrosis ( Evans et al., 2020 ) and other pharmacological effects.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal ROS levels and oxidative stress always participate in the following toxic effects induced by internal toxicants or xenobiotic exposure [ 15 , 16 ]. A previous study reported that emodin treatment promoted ROS content in the rat liver [ 17 ], but several studies found that low doses of emodin could inhibit ROS-mediated oxidative stress in HeLa cells and rat macrophages [ 12 , 18 ]. In conformity with earlier findings related to non-hepatocytes, our results demonstrated that emodin-induced ROS generation was associated with emodin-caused hepatic cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, no report is currently available that emodin induces ROS generation and the consequent ER stress- and/or mitochondrial-related apoptosis in hepatocytes. Instead, emodin (10 μ M) could inhibit oxidative stress generated by arachidonic acid plus iron [ 12 ]. Thus, the role of ROS-mediated mitochondrial dysfunction, ER stress, and related apoptotic cell death in hepatotoxicity caused by emodin needs to be explored.…”
Section: Introductionmentioning
confidence: 99%